2014
DOI: 10.1093/ejcts/ezu258
|View full text |Cite
|
Sign up to set email alerts
|

Four-year outcomes with third-generation centrifugal left ventricular assist devices in an era of restricted transplantation

Abstract: OBJECTIVESThird-generation ventricular assist devices (VADs) are associated with improved outcomes, though in recent clinical trials bridge-to-transplant (BTT) rates are ∼30% at 6 months, so that transplantation can be used as a ‘bail out’ for serious complications. In the UK, there was a significant reduction in heart transplantation rates over the last decade, so that transplantation from VADs is much less frequent. The objective of this study was to determine outcomes and their predictors in this situation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 13 publications
2
8
0
Order By: Relevance
“…The percentage of patients with ICD/ cardiac resynchronization therapy in our population is lower than in some centres outside Kazakhstan, perhaps because of the fact that cardiac electrophysiology programmes in Kazakhstan began to develop recently. The mean age of our patients was similar to other recently published LVAD experience 11,12 The proportion of our patients with a DT indication was similar to the INTERMACS database. Fifty six percent of our patients received a VAD for the BTT indication; however, because of the lack of heart donors, transplantation is not common.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The percentage of patients with ICD/ cardiac resynchronization therapy in our population is lower than in some centres outside Kazakhstan, perhaps because of the fact that cardiac electrophysiology programmes in Kazakhstan began to develop recently. The mean age of our patients was similar to other recently published LVAD experience 11,12 The proportion of our patients with a DT indication was similar to the INTERMACS database. Fifty six percent of our patients received a VAD for the BTT indication; however, because of the lack of heart donors, transplantation is not common.…”
Section: Discussionsupporting
confidence: 81%
“…Notwithstanding, the differences in our study population compared with other centres, observed survival and adverse event rates are not dissimilar to those reported by other centres. [11][12][13] Our VAD programme was developed before any heart transplantation programme existed in our country. The existence of the VAD programme is now stimulating the growth of heart transplantation in Kazakhstan.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with other series, the duration of support was longer, 2,11 which can at least partially explain the higher thrombotic event rates, because these are related to the duration of support. 4 This is also supported by the fact that our median time to PT is longer than in other series. 11 A unique aspect of our study population is the relatively low rates of transplantation in a group of patients in whom the indications were bridge to transplant or bridge to decision.…”
Section: Figuresupporting
confidence: 82%
“…This is a retrospective analysis of patients aged older than 16 years who received a HeartWare HVAD as bridge to transplant or bridge to candidacy in the Freeman Hospital, between July 2009 and August 2015, following the standard technique previously described. 9 Anti-coagulation and anti-platelet regimens have previously been described, 4 and in brief, have been since 2011 a target international normalized ratio of 2.7 and aspirin at 300 mg daily. Before that, the standard dose of aspirin was 75 mg daily.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation